Ecocultural Perspectives On Mental Well-being and Self-harmony Among Sports Science Students - Song, Peng; Wang, Shaojie; Jiang, Bo; Zhao, Lunan (Quality in Sport, 2025)
Drawing on Rogers’ humanistic psychology framework, this study explores the interplay between self-harmony and mental health among sports majors. For college students majoring in physical education, this theory serves as a significant reference for maintaining their mental well-being. This research delves into the relationship between the mental health status and self - harmony of physical education majors. By doing so, it aims to offer novel perspectives for the psychological health education and counseling tailored to this specific group of students. A random sampling approach was adopted to recruit physical education majors. Participants completed two validated instruments: the Symptom Checklist 90 (SCL-90) for assessing mental health symptoms, and the Self-Harmony Scale (SCL-HA) to measure congruence between self-concept and experiences. Data collection followed a double-blind protocol to minimize bias. The findings indicate that the disharmony between self and experience has the most profound impact on the mental health of these students, closely followed by communication - related issues. There exists a notable negative correlation between the mental health of physical education majors and the self - experience disharmony, while a significant positive correlation is observed between mental health and self - flexibility. Students with better mental health conditions exhibit remarkably higher levels of self - harmony and self - flexibility compared to those with poorer mental health. Drawing on Rogers’ humanistic psychology framework, this study explores the interplay between self-harmony and mental health among sports majors. By employing mixed-method analyses (SCL-90 and SCL-HA scales), we identify key predictors of psychological well-being and propose actionable strategies for enhancing mental health interventions tailored to this cohort.